Genetic and antigenic characterization of rabies viruses reveals transmission to cattle from both domestic and wildlife species in the North West province, South Africa - Khoane, Onkemetse Antoinette; Ngoepe, Ernest Chuene; Sabeta, Claude Taurai; Mphuti, Nthabiseng; Syakalima, Michelo (Frontiers in Tropical Diseases, 2025)
IntroductionRabies is an important veterinary and public health disease, and causes thousands of human deaths annually in the low and middle-income countries (LMICs). The aim of this study was to determine the rabies virus biotypes associated with cattle rabies by analyzing lyssavirus-infected brain tissues collected between 2008 and 2018 from the North-West province (South Africa).MethodologyA total of 43 rabies-infected brain tissues were subjected to reverse-transcription PCR of the highly variable glycoprotein gene, and the generated amplicons were sequenced. In addition, 20 cattle rabies viruses were subjected to an indirect immunofluorescent antibody test and their reactivity patterns compared to those from commonly-circulating southern African lyssaviruses.ResultsDuring the study period (2008–2018), cattle were the most commonly infected host species with rabies virus (42%), followed by domestic dogs (28%), goats (4%), sheep (3%), and a variety of wildlife species including black-backed jackals (13%), yellow mongooses (4%), slender mongooses (3%), duiker (2.1%), honey badgers (1%) and unidentified species (1%). Phylogenetic analysis of the generated nucleotide sequences delineated the rabies viruses into four clades, three belonging to the canid rabies virus biotype. The first clade comprised wildlife, domestic dog and bovine RABVs, and the second and third exclusively jackal and bovine RABVs, linked to dog and jackal RABVs from the commonly dog-endemic regions of South Africa. The fourth clade consisted of cattle RABVs associated with the mongoose rabies biotype. Phylogenetic analyses confirmed very close genetic relationships between dog and jackal RABVs, highlighting the common progenitor and historical introduction of rabies in the country, and cross-species transmission events between domestic and wildlife host species. Antigenic typing, allows us to infer the sources of RABV infection, given that antigenic variants of rabies virus are associated with different rabies cycles and species of terrestrial carnivores in South Africa.ConclusionThis study highlighted the transmission routes between domestic (dogs) and wildlife (jackals and mongooses) reservoirs and cattle. Both antigenic and genetic typing suggest interactions between livestock and both domestic and wildlife. Vaccination of dogs remains crucial to break rabies transmission cycles and particularly so in the North West of the country.